Tertiary butylhydroquinone influence over oxidation stability of biodiesel from waste cooking oil - Setyawardhani, Dwi Ardiana; Ammar, Thufeil; Ammar, Yusuf (Jurnal Rekayasa Proses, 2022)
An oxidation stability is very important for a long-term storage of biodiesel. Some physical (density and viscosity) and chemical properties (acid value, iodine value, and peroxide value) were analyzed to predict the oxidation stability for biodiesel produced from Waste Cooking Oil (WCO). WCO is one of the potential feedstocks in Indonesia, which is a large cooking oil consumer. Biodiesel from WCO was produced by transesterification process in 60 oC temperature for one hour reaction time. Methanol was added in 4:1 (v/v) ratio of WCO with 2% potassium hydroxide as a catalyst. This study observed the influence of tertiary butylhydroquinone (TBHQ), a synthetic antioxidant, on the oxidation stability of biodiesel. TBHQ was used as an antioxidant agent to prevent biodiesel oxidation for such long-term storage. It was blended with biodiesel at various concentrations (0-1200 ppm). Samples were taken every week to measure the density, viscosity, acid value, iodine value (IV) and peroxide value (PV) during the storage process of the biodiesel blends which was conducted for 4 weeks. The experimental results revealed that an improvement in oxidation stability was achieved in all TBHQ concentrations. All parameters meet Indonesia’s National Standards (SNI) for biodiesel added with TBHQ up to 1200 ppm. Biodiesel which was treated with 1200 ppm of TBHQ provided the best result, due to its density, viscosity, IV, and PV. However, TBHQ addition was did not affect the free fatty acid and acid number for 4 weeks of storage.